Comparing outpatient oral antibiotic use in Germany and the Netherlands from 2012 to 2016. Issue 12 (28th September 2018) - Gradl, Gabriele; Teichert, Martina; Kieble, Marita; Werning, Johanna; Schulz, Martin
Abstract: Purpose: Overuse of antibiotics is of concern, but may differ between European countries. This study compares outpatient use of oral antibiotics between Germany (DE) and the Netherlands (NL). Methods: For DE, we used the DAPI database with information on dispensings at the expense of the Statutory Health Insurance Funds from > 80% of community pharmacies. For NL, data were obtained from the Dutch Foundation for Pharmaceutical Statistics. Use of oral antibiotics was estimated as defined daily doses per 1000 inhabitants per day (DID), except for age comparisons as packages per 1000 inhabitants annually. National time trends were assessed with linear regression, stratified for the major antibiotic classes, and individual substances. Results: From 2012 to 2016, outpatient antibiotic use was lower in NL than in DE (9.64 vs 14.14 DID in 2016) and non‐significantly decreased slightly over time in both countries. In DE, dispensings of oral antibiotics to children were higher compared with NL for the age groups 2 to 5 (2.0‐fold in 2016) and 6 to 14 years (2.7‐fold in 2016). Use of cephalosporins was very low in NL (0.02 DID in 2016), but the second most frequently dispensed class in DE (2.95 DID in 2016). Conclusion: From 2012 to 2016, outpatient use of oral antibiotics was lower in NL than in DE. Differences were primarily observed in the age groups 2 to 5 and 6 to 14 years, although the recommendations of evidence‐based guidelines in both countries were in agreement.